Economics / Principles, Problems, and Policies: Fourteenth Edition - Brue Stanley L; Mcconnell Campbell R (Irwin Mcgraw-Hill, 1998)
Preface, An Introduction to Economics and the Economy, National Income and Employment and Fiscal Policy, Money and Banking and Monetary Policy, Problems and Controversies in Macroeconomics, Microeconomics of Product Markets, Microeconomics of Government, Microeconomic Issues and Policies, International Economics and the World Economy, Glossary, Index.